Quality of the Italian Websites for Parental Guidance on the Indications for Tonsillectomy in Children - Corrêa, Camila De Castro; Piña, Sofia Prata [UNESP]; Evangelisti, Melania; Villa, Maria Pia; Weber, Silke Anna Theresa [UNESP] (Thieme, 2020)
Introduction  The quality of information on websites about tonsillectomy regarding the knowledge level may be low. Tonsillectomy is a surgical procedure to hypertrophy of the palatine and pharyngeal tonsils. So, it is an invasive procedure with possible complications, which creates insecurity in parents. Significantly, Internet searches have been increased to address possible health concerns, questioning the quality of websites about tonsillectomy. Objective  To evaluate the readability, reliability, and comprehensiveness of the Italian websites dedicated to parental guidance regarding the indications for tonsillectomy in children. Methods  The search engine google.it was used to search the websites. The Gulpease index, which is a widely used readability formula ranging from 0 (difficult) to 100 (easy readability), was employed to evaluate these websites. The Health on the Net Code of Conduct (HONcode) was used to assess the quality of information, by taking ethical principles into account, with values ranging from 0 to 13. The content comprehensiveness of the web pages was assessed by assigning points ranging from 1 (very insufficient) to 5 (very satisfying) to each page. A final comparison with previous studies on tonsillectomy published on websites from other countries was performed. Results  Fourteen Italian websites were selected, and the Gulpease index showed a mean average of 40.77 ± 8.45. The mean of the HONcode analysis was 6.00 ± 1.92, in which the principles with the poorest scores were Attribution and Update. As far as the comprehensiveness of the websites is concerned, the resulting mean was 2.57 ± 0.77, in which Indications was the topic with the highest mean, whereas Benefits was the one with the lowest. Conclusion  The Italian websites were characterized by a lower readability level, a middle position regarding ethical principles, and the same (insufficient) comprehensiveness of tonsillectomy when compared with websites from different countries.
Keywords: internet; patient information; patient portals; readability; tonsillectomy